ANALYSIS OF THE EFFECT OF THE DEMOGRAPHIC BONUS ON ECONOMIC GROWTH IN NORTH SUMATRA 2015-2021 - Alwi, Haddad; Purnomo, Diki; Tonggo Purba, Nico William; Denvico Tamba, Noel Ramot (Quantitative Economics Journal, 2023)
This study aims to determine whether the Demographic Bonus affects Economic Growth in North Sumatra Province. Annual data related to the Demographic Bonus from 2015 to 2021 is used. The method used in this study is multiple linear regression method. This type of research is descriptive quantitative with secondary data obtained from the Central Bureau of Statistics of North Sumatra Province. The results of the study found that the variable Labor Force Participation Rate has a positive and significant effect on economic growth in North Sumatra, this is due to when there is an increase in the labor force in North Sumatra balanced with an increase in job absorption. And  the Dependency Ratio has a positive and significant effect on economic growth.